Fusobacterium necrophorum leukotoxoid vaccine for prevention of liver abscesses - S. Saginala; K.F. Lechtenberg; Kenneth E. Kemp; P.M. Hine; Tiruvoor G. Nagaraja; M. M. Chengappa (Kansas Agricultural Experiment Station Research Reports, 1998)
The efficacy of Fusobacterium necrophorum crude leukotoxoid vaccine to immunize and protect steers against experimentally induced liver abscesses was evaluated. The vaccine consisted of cell-free culture supernatant of a high leukotoxin-producing strain of F. necrophorum, inactivated with formalin and homogenized with an oil emulsion adjuvant. Vaccine was injected subcutaneously on days 0 and 21. Blood samples were collected weekly to monitor immune response. Three weeks after the second vaccination, steers were injected intraportally with F. necrophorum culture to induce liver abscesses. Three weeks later (day 63), steers were euthanatized and necropsied; livers were examined, and protection was assessed. Anti-leukotoxin antibody titers in the control steers generally did not differ from the baseline (week 0) titers. The titers in the vaccinated groups increased, more so after the second injection, and the increase was generally dose dependent. At necropsy, all steers in the control group had liver abscesses. In the vaccinated groups, two out of five steers in the 1.0 ml group and one each in the 2.0, 5.0, and 2.25 ml (concentrated) groups had liver abscesses. The difference suggests a protective effect of antileukotoxin antibodies against experimentally induced liver abscesses.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Liver abscesses; Fusobacterium necrophorum; Leukotoxoid vaccine